PEMANFAATAN TEKNOLOGI GOOGLE MAPS PADA MATERI MITIGASI BENCANA DALAM PEMBELAJARAN GEOGRAFI SMA NEGERI DI KECAMATAN KOTO TANGAH KOTA PADANG - Azura, Intan; Bayu Wijayanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal utilization of Google Maps technology in geography learning on disaster mitigation material in Public Senior High Schools in Koto Tangah District, Padang City. The study aims to analyze the utilization of Google Maps in geography learning, determine teacher and student perceptions of its use, and identify supporting and inhibiting factors in its implementation. The study used a mixed method approach with a sequential explanatory design. The study population was all eleventh-grade students and geography teachers at four Public Senior High Schools in Koto Tangah District, Padang City. The research sample consisted of 120 students selected using purposive sampling techniques and 4 geography teachers as informants. Data collection techniques included questionnaires, interviews, observation, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data condensation, data presentation, and conclusion drawing. The results showed that the utilization of Google Maps in geography learning on disaster mitigation material has been implemented, but not optimally. Teachers and students gave positive perceptions towards the use of Google Maps because it is able to improve spatial understanding, learning motivation, and student engagement in learning. The main obstacles faced include limited technological facilities and infrastructure, uneven distribution of teachers' digital competencies, and limited internet access.